2014
DOI: 10.1128/jvi.01477-14
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Specificities, Phenotypes, and Antiviral Activities of Cytomegalovirus-Specific CD8+T Cells

Abstract: CD8؉ T cells specific for pp65, IE1, and IE2 are present at high frequencies in human cytomegalovirus (HCMV)-seropositive individuals, and these have been shown to have phenotypes associated with terminal differentiation, as well as both cytokine and proliferative dysfunctions, especially in the elderly. However, more recently, T cell responses to many other HCMV proteins have been described, but little is known about their phenotypes and functions. Consequently, in this study, we chose to determine the divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 67 publications
1
76
0
Order By: Relevance
“…In this regard, the CD8 T-cell lines examined in the current study were derived from blood T cells harvested 15 days after virus challenge of animals previously vaccinated with a live attenuated vaccine. Previous longitudinal studies of CD8 T-cell responses to human CMV and EBV indicated that the range of CD8 T-cell specificities remains relatively stable over time [13,46,47], although in some instances a less pronounced dominance hierarchy has been observed in the memory pool compared to the active response [48]. It is possible that the detection in the current study of prominent responses to BHV-1 IE proteins reflects preferential expansion of pre-existing memory T cells specific for the IE antigens in the 15-day period immediately following virus challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the CD8 T-cell lines examined in the current study were derived from blood T cells harvested 15 days after virus challenge of animals previously vaccinated with a live attenuated vaccine. Previous longitudinal studies of CD8 T-cell responses to human CMV and EBV indicated that the range of CD8 T-cell specificities remains relatively stable over time [13,46,47], although in some instances a less pronounced dominance hierarchy has been observed in the memory pool compared to the active response [48]. It is possible that the detection in the current study of prominent responses to BHV-1 IE proteins reflects preferential expansion of pre-existing memory T cells specific for the IE antigens in the 15-day period immediately following virus challenge.…”
Section: Discussionmentioning
confidence: 99%
“…However, certain proteins tend to be recognized more consistently and generate stronger responses than others, eg. pp65 and IE1 in CMV [13]. Analyses of CD8 T cells from humans infected with herpes simplex virus type 1 (HSV-1), an alpha herpesvirus most closely related to BHV-1, have identified CD8 T-cell reactivity with over half the viral proteins, including proteins with diverse expression dynamics [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A UL83 (pp65) ORF 15-mer peptide library was synthesized by JPT Peptide Technologies GmbH (Berlin, Germany). The individual lyophilized peptides from each ORF library were reconstituted and used as previously described (54).…”
Section: Ethicsmentioning
confidence: 99%
“…Regarding this, knowledge of specific viral proteins to which CMV-specific CD4 + cells respond would be informative but is not currently available and was beyond the current study's scope. However, of relevance, many healthy CMV-seropositive individuals control CMV effectively with a CD8 + T cell repertoire predominantly directed against early-expressed viral proteins, rather than later structural components (22 …”
Section: Cd4mentioning
confidence: 99%